Efisiensi Tanda Tangan Elektronik dalam Pelayanan Adminduk Daring di Disdukcapil Kabupaten Wonogiri - Aulia Athaya (Universitas Sebelas Maret, 2021)
This paper aimed to analyze the service standard of implementation electronic signature by Telunjuk Sakti for the efficiency online population administration services in Population and Civil Registration Office Wonogiri District. The research used empirical juridical research. The result shows that law enforcement in this service has not been successful due to community ang cultural factors. This factor is due because public have less awareness the importance of family register and the various functions electronic signature and public also have less understanding of technological development. Next, the efficiency of this service is less seccessful because there are conditions for achieving work efficiency not been fulfilled is real division of labor. This happens because many older employees don’t understand technological developments, so that jobs are transferres to young employees. Obtacles factor that often occours is damage of internet network on service system.Keyword: Electronic Signature, Telunjuk Sakti, Family Register.